Illegitimacy in Eighteenth-Century Wales. (14th July 2013) - Muir, Angela
Census returns and the Reports of the Commission of Enquiry into the State of Education in Wales (1847) reveal that in comparison with England certain parts of Wales experienced a significantly higher level of illegitimacy in the nineteenth century. This article seeks to demonstrate that increased illegitimacy existed in some parts of Wales at least a century and a half prior to the 'Blue Books' and that this was the result of courtship customs and marital traditions that were unique to Wales. Evidence of paternity in parish baptism registers allows for a distinction to be made between illegitimacy that resulted from permissible sexual relationships and illicit sexual encounters. Behaviour leading to illegitimacy can be categorized into four different types of sexual behaviour, of varying degrees of acceptability and stigmatization, based on the ways in which fathers are listed. When this typology is applied to the baptism registers of the parishes of St Peter's in Carmarthenshire and Hawarden in Flintshire it becomes clear that higher rates of illegitimacy in Wales were probably the result of socially acceptable relationships that may not have been condoned by ecclesiastical authorities, rather than illicit sexuality that was not generally condoned by communities or the authorities.